STUDI DINAMIKA KUALITAS AIR DAS CILIWUNG - Soewandita, Hasmana; Sudiana, Nana (Jurnal Air Indonesia, 2010)
Ciliwung River which has upstream in Bogor, while downstream in Jakarta presence has very important role for the region in its path. Positive role of the river for the public interest in this area include the need of clean water sources, irrigation / agriculture, industry and others. Conversely Ciliwung River is also a source of flood disaster in Jakarta. Will consider its use, the risk of disaster resources and environmental burdens are received by the waters and the water catchment area is very large, then the existence of river quality should be monitored both the water catchment conditions or water quality. For future purposes, it would require a management with specific deadlines (5 th, 10 th, 15 th) and targets based on the quality of the water quality standards (BMA) class III, II and I. The results of the current monitoring parameters BOD, COD, fecal Coli, Coliform has a value above the threshold of water quality standards specified. While DO in the downstream segment has a value below the water quality standards. Other parameters such as pH, TSS and nitrogen have a greater trend downstream, but the value of the water quality is still under water quality standards that are targeted.Ã‚Â Keywords: Water quality, Water Quality standards, Ciliwung river.